Pembuatan kitosan dari kulit dan kepala udang laut perairan kupang sebagai pengawet ikan teri segar - Mamiek Mardyaningsih; Aloysius Leki; Oktovianus D. Rerung (Jurnal Rekayasa Proses, 2014)
The objective of the study is to examine the feasibility of chitosan from skin and head of the shrimp from Kupang seas as a fresh anchovy preservative. The study was conducted through two stages: chitosan production and application of chitosan as fresh anchovy preservative. Chitosan production generally starts from shrimp waste flour manufacture, deproteinization, demineralization and deacetilation. The concentration of chitosan as fresh anchovy preservative is 1.5%. Chitosan characterization includes water, protein, ash and fat and fresh anchovy test which covers the organoleptic test, microbiology and proximate test. The results showed that chitosan has flake shape with moisture content of 2.81%, ash 0.75%, nitrogen 7.26%, clear transparent color and 79.11% degree of deacetilation. Characteristics of chitosan meet Proptan Laboratoris standards. Storage life of fresh anchovy soaked in chitosan is 3 days at room temperature storage, while for normal fresh anchovy is only 1 day. Chitosan can extend the storage life, increase the rate of protein fish, preserve the taste of fresh anchovy and make the fresh anchovy more shinny.